Military Responses to the Arab Uprisings and the Future of Civil-Military Relations in the Middle East Analysis from Egypt, Tunisia, Libya, and Syria - Taylor, William C.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
This book explains Arab military responses to the social uprisings which began in 2011. Through a comparative case study analysis of Egyptian, Tunisian, Libyan, and Syrian militaries, it explains why militaries fractured, supported the regime in power, or removed their presidents.
Keywords: Political science; Ethnology -- Middle East; Democracy; Middle East -- Politics and government; International relations; Politics and war; Political Science and International Relations; Democracy; Middle Eastern Politics; International Relations; Middle Eastern Culture; Political Science; Military and Defence Studies